Broadband LEO Constellations for Navigation. Issue 2 (25th June 2018) - Reid, Tyler G.R.; Neish, Andrew M.; Walter, Todd; Enge, Per K.
Abstract: There has been resurgent interest in building low Earth orbiting (LEO) constellations of satellites on a new scale. Their aim is Internet for the world with plans for potentially thousands of satellites. Here, we explore how these LEO constellations can be utilized for navigation. Closer to Earth, LEO offers stronger signals, strengthening us against jamming and aiding in indoor and urban environments. Proximity is also its weakness, where satellites have a small Earth footprint requiring many to provide global coverage. We show that the strength of the Broadband LEO constellations is their numbers, where they offer threefold improvement in satellite geometry compared to navigation core‐constellations today. This allows for relaxation of the signal‐in‐space user range error, while still matching the position accuracy of GPS. Coupled with the more benign radiation environment in LEO compared to GPS in medium Earth orbit, this enables a navigation payload designed using commercial‐off‐the‐shelf components. © 2018 Institute of Navigation